(untitled) (Research, Society and Development, 2022)
Introduction: The current health approach advocated by the Unified Health System (SUS) is no longer restricted to the disease-centered view, but to a work that aims at comprehensiveness, considering the subject, the environment, the lifestyle and the promotion of health. Thus, there is a need to introduce care focused on health care. Objectives: to verify the understanding and level of application of reception by health professionals working in the ESF units in the Municipality of Itaboraí, in Rio de Janeiro. Methodology: This is a descriptive-analytical study that focuses on the welcoming activities carried out by health professionals in Basic Health Units. Results: the sample consisted of 57 professionals with a predominance of females, a predominance of community health workers, who reported that embracement is welcoming the other and seeking to give them guidance, applying embracement frequently in their work units. Final considerations: the professionals involved with the ESF have technical knowledge on the subject, in addition to applying them in practice, making care more humane, effective and more specific, according to the needs of each individual.